ISSUES OF IMPROVING THE LEGAL FRAMEWORK FOR STATE CONTROL AND VERIFICATION OF COMPLIANCE WITH LABOR RIGHTS OF EMPLOYEES - Javokhir, Turaev (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
this article analyzes the norms of the Constitution and legislative acts adopted in the new edition as the legal basis for state control and inspection of compliance with labor rights of employees. In particular, systemic problems in the norms of the law are studied based on the experience of the legislation of foreign countries. In the article, the author substantiates the need to improve legislation, in particular, to develop and adopt the law "On state control of the activities of business entities".